2009
DOI: 10.1002/poc.1567
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of mixed organozinc and mixed organocopper reagents. Part 4: a kinetic study of group transfer selectivity in CC coupling of mixed diorganocuprates

Abstract: The competitive rate data and Taft relationships for the coupling of bromomagnesium n-butyl (substituted phenyl) cuprates with alkyl bromides show that selective n-butyl transfer can be explained by an oxidative addition mechanism. Taft reaction constants also show that the residual group FG-C 6 H 4 in the mixed cuprate n-Bu(FG-C 6 H 4 )CuMgBr changes the ability of the copper nucleophile to react with the electrophile RBr. These results provide support for the commonly accepted hypothesis regarding the depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…We were surprised to see that the selective transfer of n-Bu group in the alkylation of stoichiometric bromomagnesium n-butylphenylcuprate, n-BuPhCuMgBr at room temperature [42] gets reversed in the CuI catalyzed alkylation of bromomagnesium zincate n-BuPh 2 ZnMgBr 1ab 2 at reflux temperature and also a preference for transfer of Ph group over n-Bu group is observed in the CuI catalyzed alkylation of bromomagnesium zincate n-Bu 2 PhZnMgBr 1a 2 b. Before discussing the formation and reaction of active organocopper intermediates in the reactions of copper catalyzed zincates, we made a literature survey on the structure of triorganozincates.…”
Section: Entrymentioning
confidence: 97%
See 1 more Smart Citation
“…We were surprised to see that the selective transfer of n-Bu group in the alkylation of stoichiometric bromomagnesium n-butylphenylcuprate, n-BuPhCuMgBr at room temperature [42] gets reversed in the CuI catalyzed alkylation of bromomagnesium zincate n-BuPh 2 ZnMgBr 1ab 2 at reflux temperature and also a preference for transfer of Ph group over n-Bu group is observed in the CuI catalyzed alkylation of bromomagnesium zincate n-Bu 2 PhZnMgBr 1a 2 b. Before discussing the formation and reaction of active organocopper intermediates in the reactions of copper catalyzed zincates, we made a literature survey on the structure of triorganozincates.…”
Section: Entrymentioning
confidence: 97%
“…We reported that selective n-butyl transfer takes place in the alkyl coupling of bromomagnesium n-butyl-phenylcuprate, n-BuPhCuMgBr in THF [42]. In addition, our kinetic work on the coupling of n-BuRCuMgBr (R ¼ substituted phenyl) with alkyl bromides showed that selective n-butyl transfer can be explained by an oxidative mechanism and the residual group changes the ability of the copper nucleophile to react with the electrophile.…”
Section: Introductionmentioning
confidence: 96%
“…In their systematic work, Erdik and coworkers observed that the group selectivities of mixed diorganocuprates, R 1 R 2 CuM (MMgBr), ZnI, diorganozincs, R 1 R 2 Zn, and Cu‐catalyzed mixed triorganozincates, R 1 (R 2 ) 2 ZnMgBr, depend on the reaction parameters, that is, the electrophilic substrate, the solvent, and the temperature as well as the transition metal catalyst and organocatalyst, and reported that the group selectivity of mixed organocopper and organozinc reagents can be controlled by changing the reaction parameters. They also developed new atom‐economic synthetic procedures for CC, C‐acyl, and CN coupling employing mixed arylzinc reagents. However, probing the origin of group selectivity in the mixed organocopper and organozinc reagents still seems a problem.…”
Section: Introductionmentioning
confidence: 99%
“…In connection with my recent studies on the control of group selectivity in acylation of n ‐alkylphenylzinc reagents and kinetics of acylation of iodozinc alkylarylcuprates, I focused my interest on the acylation of n ‐alkylarylzinc reagents with the objectives of kinetics and mechanism of phosphine‐catalyzed acylation of diorganozincs and providing another kinetic support for Erdik's hypothesis regarding the dependence of R T group transfer ability on R R group in reactions of R R R T Zn reagents. According to the best of my knowledge, there is a limited number of reported work on the kinetics of reactions of uncatalyzed and Cu(I)‐ and Ni(II)‐catalyzed reactions of monoorganozincs and diorganozincs. A theoretical study for transfer ability in mixed diorganozincs has been also published .…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the presence of a moiety capable of chelating Li ions destabilized the mixed cuprate p complex and promoted the metathesis reaction. [20] The observation of small cis and large trans two-bond coupling across Cu in the NMR spectra of cuprate-thiocarbonyl complexes suggests a pseudo square planar arrangement of ligands, [15,21] which in turn implies a significant degree of Cu III character. [18] The second major factor that influences the structures of mixed cuprates with dummy ligands such as cyano, alkynyl, and thiolato was identified as a structural trans effect ("trans influence").…”
mentioning
confidence: 99%